МУСИҚА ЎҚИТУВЧИЛАРИНИ КАСБИЙ ТАЙЁРЛАШНИНГ ИЛМИЙ - ПЕДАГОГИК АСОСЛАРИ - Халилов, Ф.Н. (SCIENCE and SOCIETY, 2020)
This article is devoted to the problem of developing professional knowledge and shills of music teachers.
Keywords: music art; creative means; art; enlightenment; song; melody; method; facility; articles of music teachers